2012
DOI: 10.2478/s11534-012-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric pitch-transitions induced by a magnetic field in a sample containing incomplete number of pitches

Abstract: Abstract:We investigate the pitch transitions induced by an external bulk field in a Cholesteric Liquid Crystal slab of finite thickness that contains an incomplete number of π-twists. The analysis is performed for a magnetic field that is (i) perpendicular to the helical axis, and (ii) tilted with respect to one of the easy directions imposed by planar and rigid boundary conditions. For finite we obtain a cascade of transitions, where the bulk expels a half-pitch at a time with increasing field to avoid diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…More recently, Scarfone et al [20] generalize the problem of [19] to consider an in-plane magnetic field tilted at some angle with respect to fixed parallel twist directions on the substrates. The analysis of Lelidis et al [21] allows for an incomplete number of half twists in the liquid crystal layer by imposing strong homogeneous anchoring with non-parallel director twists on the two confining plates.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Scarfone et al [20] generalize the problem of [19] to consider an in-plane magnetic field tilted at some angle with respect to fixed parallel twist directions on the substrates. The analysis of Lelidis et al [21] allows for an incomplete number of half twists in the liquid crystal layer by imposing strong homogeneous anchoring with non-parallel director twists on the two confining plates.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a natural continuation of the previous studies [28,29], where a cell of CLC with finite thickness with a strong anchoring at the limiting surfaces is perturbed by an external field. In that case it also has been shown how the system expels twists one by one in a sequence that accumulates toward the critical value, signifying the CLC → NLC final transition.…”
Section: Discussionmentioning
confidence: 72%
“…In Refs. [28,29], we have generalized previous studies, relevant to the CLC → NLC transition induced by a magnetic field, by assuming strong anchoring on the limiting surfaces of the cell. In this framework, it has been shown that, as the external field increases in its strength, the system expels one twist at a time until a certain critical value is reached, beyond which the system passes from the cholesteric to the nematic phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability mechanism underlying the pitch transitions has been discussed by Kiselev and Sluckin in [10]. Recently, Scarfone et al [11,12] have shown that in the limit of infinite thickness the analysis presented in [3,4] yields the results reported in [1]. Experimental observations of CLC pitch transitions have been reported in [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%